Toxocara seroprevalence in schizophrenic patients in Turkey - Kaplan, Mustafa; Kalkan, Alunet; Kuk, Salih; Demirdag, Kutbeddin; Ozden, Mehmet; Kilic, S. Sirri (Yonsei Univ Coll Medicine, 2008)
Purpose: To investigate the seroprevalence of toxocariasis in patients diagnosed as schizophrenia. Patients and Methods: Ninety-eight schizophrenic patients hospitalized at The Elazig Psychiatric Hospital were included in the study. Anti-Toxocara IgG and/or IgM antibodies were determined by using commercial Toxocara canis IgG and/or IgM ELISA kit. Results: Seropositivity for T canis was detected in 45 (45.9%) of 98 patients and 2 (2.0%) of 100 control subjects the difference was statistically significant (p < 0.001). The seroprevalence was 40.4% (19 cases) and 51.0% (26 cases) for female and male subjects, respectively (p = 0.3). When the seropositive and seronegative schizophrenic patients were compared with respect to the age group environment they were living in, occupation period of follow up and number of hospitalizations, there were no differences between the two groups (all, p > 0.05). Conclusion: In conclusion, the schizophrenic state seems to present a high risk for Toxocara infection in Turkey.
Keywords: toxocariasis; seroprevalence; schizophrenic patients